Evaluation of the accuracy of numerical calculations of reliability models filtration wet particulate materials - Лисогор, Василь Микитович; Зелінська, Оксана Владиславівна (Eastern-European Journal of Enterprise Technologies, 2013)
Proposed and developed approaches to assess the accuracy of numerical calculations of reliability and filtration efficiency models moist particulate materials alhorytmaty protect the internal structure of materials from mechanical damage. Recognized published monographs, books and periodical sources of study subjects. A closer analysis shows that the effectiveness of filtering moist disperse materials can be improved by using the method of local random search or algorithmic model identification multistage random search process. The effectiveness of filtering also can be improved through the use of expert systems developments, where methods and researches of various objects which function in the conditions of vagueness. Filtering moist disperse materials precisely characterized by considerable uncertain of their behavior. Also known the source, where the problematic issues of reliability of machines during the design, manufacture their commercial operation. Considered interconnected complex problems: friction, wear old. Disclosed causes changes in the technical condition of machines and physics of failure. An approach assessing the reliability of performance conditions breakage automated chemical process. Summarizing written, it is clear that there are both fundamental and recurring sources where published results Vibropress equipment. However, virtually no publications to assess the accuracy of numerical calculations of reliability and efficiency filtration moist disperse materials in agriculture. In connection with this subject of the article is quite relevant.